All-solid-state battery and manufacturing method thereof
By forming a sulfide-based solid electrolyte layer with different chemical compositions on the positive electrode and negative electrode of an all-solid state battery, and making it face-to-face contact, the physical peeling problem of the electrode and the solid electrolyte layer is solved, and the mechanical strength and electrochemical stability are improved , achieving improvements in the performance and manufacturing efficiency of all solid-state batteries.
Patent Information
- Application Number
- CN202410386008.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-21
- Filing Date
- 2024-04-01
- Publication Date
- 2025-02-21
AI Technical Summary
In the manufacturing process of existing all-solid state batteries, there are problems with physical falloff between electrodes and solid electrolyte layers, and the large resistance of the porous polymer support leads to a decrease in performance and process efficiency.
By forming a sulfide-based solid electrolyte layer with different chemical compositions on the positive electrode and the negative electrode, and making it face-to-face contact, the electrochemical stability at the interface between the electrode-solid electrolyte layer is ensured and the mechanical strength is improved.
The stable combination of the electrode and the solid electrolyte layer is achieved, preventing physical falloff, improving mechanical strength and electrochemical stability, and improving the performance and manufacturing efficiency of all-solid state batteries.
Smart Images

Figure CN119495805A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an all-solid-state battery with a structure in which different types of sulfide-based solid electrolyte layers are in face-to-face contact, and a method for manufacturing the same. Background Art
[0002] Currently, unprecedented climate change is taking place around the world, and in order to solve these environmental problems, countries are continuously working to achieve carbon neutrality. Carbon neutrality refers to minimizing greenhouse gas emissions and absorbing emitted greenhouse gases through various methods to make greenhouse gas emissions essentially zero (0). This ultimately led to a movement to curb the use of fossil fuels and expand the use of new renewable energy. In order to utilize new renewable energy, energy storage is necessary, and batteries can be used as the main means of energy storage. In the case of automobile production, there is a move towards reducing the use of existing internal combustion engines that use fossil fuels and expanding the popularity of electric vehicles (EVs) that use batteries.
[0003] Electric vehicles generally use lithium secondary batteries with high energy density. Lithium secondary batteries using liquid organic electrolytes have a problem that heat accumulates inside the battery when operating at high temperatures, causing a very high risk of fire. Therefore, as an alternative to existing lithium secondary batteries using liquid organic electrolytes, all-solid-state batteries that prevent electrolyte leakage and significantly reduce the risk of fire and explosion by using solid electrolytes have been actively researched and developed.
[0004] Solid electrolytes generally use materials of polymer-based solid electrolytes, oxide-based solid electrolytes, and sulfide-based solid electrolytes. Among them, polymer-based solid electrolytes have the advantages of low price, material flexibility, easy processability, battery stability, electrolyte layer and battery thin filmization, etc., and are therefore widely used, but there is a problem of damage during the manufacture of batteries due to weak strength. Therefore, a technology is proposed that can be used to manufacture a solid electrolyte membrane by mixing a porous polymer support and a solid electrolyte to improve its mechanical strength, but due to the large resistance of the porous polymer support, not only will the performance of the all-solid-state battery be reduced, but the problem of reduced efficiency of the manufacturing process of the composite of the porous polymer support and the solid electrolyte remains a problem to be solved.
[0005] Therefore, it is necessary to develop a technology that can maintain the excellent performance of all-solid-state batteries while improving the process efficiency of all-solid-state batteries. Summary of the invention
[0006] Technical issues to be solved
[0007] The present invention aims to solve the above-mentioned problems and aims to provide an all-solid-state battery and a method for manufacturing the same, wherein the all-solid-state battery stably forms a solid electrolyte layer on each electrode, which not only prevents the physical detachment of the electrode and the solid electrolyte layer, but also forms a solid electrolyte layer with excellent mechanical strength, and forms different solid electrolyte layers on each electrode and makes them contact face to face, thereby ensuring the electrochemical stability at the interface between the electrode and the solid electrolyte layer and improving the performance.
[0008] Technical Solution
[0009] According to one embodiment of the present invention, an all-solid-state battery is provided, comprising: a positive electrode stack portion, the positive electrode stack portion comprising a positive electrode and a first external solid electrolyte layer formed on at least one side of the positive electrode; and a negative electrode stack portion, the negative electrode stack portion comprising a negative electrode and a second external solid electrolyte layer formed on at least one side of the negative electrode, wherein the first external solid electrolyte layer of the positive electrode stack portion and the second external solid electrolyte layer of the negative electrode stack portion are in face-to-face contact with each other, and the first external solid electrolyte layer and the second external solid electrolyte layer contain sulfide-based solid electrolytes having chemical compositions different from each other.
[0010] In addition, according to another embodiment of the present invention, a method for manufacturing an all-solid-state battery is provided, which includes the following steps: forming a positive electrode stacking portion having a first external solid electrolyte layer provided on at least one side of a positive electrode; forming a negative electrode stacking portion having a second external solid electrolyte layer provided on at least one side of a negative electrode; and bringing the first external solid electrolyte layer of the positive electrode stacking portion and the second external solid electrolyte layer of the negative electrode stacking portion into face-to-face contact with each other and rolling, wherein the first external solid electrolyte layer and the second external solid electrolyte layer contain sulfide-based solid electrolytes having different chemical compositions from each other.
[0011] Beneficial Effects
[0012] The all-solid-state battery of the present invention directly forms a solid electrolyte layer at each electrode, so that the physical detachment of the electrode and the solid electrolyte layer can be prevented through the stable combination of each electrode and the solid electrolyte layer, and a solid electrolyte layer with excellent mechanical strength can be achieved.
[0013] In addition, according to the method for manufacturing an all-solid-state battery of the present invention, by forming different solid electrolyte layers on each electrode and bringing them into face-to-face contact, the electrochemical stability at the interface between the electrode and the solid electrolyte layer can be ensured, and an all-solid-state battery with improved performance can be manufactured with high efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 is a diagram schematically showing a manufacturing process of an all-solid-state battery according to one embodiment of the present invention.
[0015] Figure 2 is a flow chart illustrating a method of manufacturing an all-solid-state battery according to one embodiment of the present invention.
[0016] Figure 3 is a graph showing charge and discharge curves of the all-solid-state batteries according to Examples 1 to 3 and Comparative Example 1.
[0017] Figure 4 Graphs showing capacity changes of all-solid-state batteries according to Examples 1 to 3 and Comparative Example 1 as cycles progress. DETAILED DESCRIPTION
[0018] The following is a detailed description of an all-solid-state battery and a method for manufacturing the same so that those skilled in the art can easily implement the present invention.
[0019] According to one embodiment of the present invention, an all-solid-state battery includes: a positive electrode stacking portion, the positive electrode stacking portion including a positive electrode and a first external solid electrolyte layer formed on at least one side of the positive electrode; and a negative electrode stacking portion, the negative electrode stacking portion including a negative electrode and a second external solid electrolyte layer formed on at least one side of the negative electrode, wherein the first external solid electrolyte layer of the positive electrode stacking portion and the second external solid electrolyte layer of the negative electrode stacking portion are in face-to-face contact with each other, and the first external solid electrolyte layer and the second external solid electrolyte layer contain sulfide-based solid electrolytes having chemical compositions different from each other.
[0020] The first external solid electrolyte layer of the positive electrode laminate and the second external solid electrolyte layer of the negative electrode laminate can be in contact with each other in a manner that they cannot be physically separated (fall off). That is, after separately manufacturing a positive electrode formed with a first external solid electrolyte layer and a negative electrode formed with a second external solid electrolyte layer, the first external solid electrolyte layer and the second external solid electrolyte layer are brought into face-to-face contact, so that the positive electrode or negative electrode can be bonded to the first external solid electrolyte layer and the second external solid electrolyte layer formed on one side thereof so that they are not mixed with each other and maintain independent forms and components, while maintaining sufficient bonding force without being physically separated (falling off) from each other.
[0021] The sulfide-based solid electrolyte may include a compound having an argyrodite crystal structure. In particular, when the substitution rate of the Group 17 element at the 4a and 4c positions in the argyrodite crystal structure is increased to the highest, lithium ion conductivity may be maximized.
[0022] The positive electrode may include a positive electrode active material and a first internal solid electrolyte.
[0023] The first inner solid electrolyte and the first outer solid electrolyte may each independently include a compound represented by Chemical Formula 1 below.
[0024] [Chemical formula 1]
[0025] M 1 6-a M 2 M 3 5-a+b X 1+a-2b
[0026] (In the chemical formula 1, M 1 is at least one selected from Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba and mixtures thereof, M 2 is at least one selected from P, N, Al, Si, Ga, Ge, As, In, Sn, Sb, Pb, Bi and mixtures thereof, M 3 is S, O or a mixture thereof, X is one or more elements selected from Group 17 elements, -1≤a<0.3, -0.2≤b≤0. )
[0027] In addition, the positive active material may include a compound represented by the following Chemical Formula 2.
[0028] [Chemical formula 2]
[0029] Li 1+c M 4 x M 5 y M 6 z O d
[0030] (In the chemical formula 2, -0.05≤c≤0.2, 2≤d≤2.02, 0≤x≤1, 0≤y≤0.5, 0≤z≤0.5, x+y+z=1, M 4 、M 5 and M 6 is at least one selected from Ni, Co, Mn, Na, Mg, Ca, Ti, V, Cr, Cu, Zn, Ge, Sr, Ag, Ba, Zr, Nb, Mo, Al, Ga and B. )
[0031] The positive electrode may be manufactured by coating a slurry for a positive electrode including a positive electrode active material, a first internal solid electrolyte, a binder, a conductive material, a dispersant, a solvent, and the like on a positive electrode collector.
[0032] The binder may include, for example, one or more selected from polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, EPDM rubber, sulfonated EPDM rubber, styrene-butadiene rubber, fluororubber, and copolymers thereof.
[0033] The conductive material may include graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, etc.; conductive fibers such as carbon fiber or metal fiber; metal powders such as aluminum and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc., but are not necessarily limited to these. Any material can be used as long as it is a conductive material that does not cause chemical changes to the battery.
[0034] The dispersant may be a water-based dispersant or an organic dispersant such as N-methyl-2-pyrrolidone (NMP).
[0035] The solvent may be, for example, one selected from toluene, xylene, naphtha, benzene, chlorobenzene, and a mixed solvent thereof, but is not necessarily limited thereto.
[0036] The positive electrode current collector may be made of, for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or a material obtained by surface-treating the surface of aluminum or stainless steel with carbon, nickel, titanium, silver, or the like.
[0037] The negative electrode may include a negative electrode active material and a second internal solid electrolyte.
[0038] The second inner solid electrolyte and the second outer solid electrolyte may each independently include a compound represented by Chemical Formula 3 below.
[0039] [Chemical formula 3]
[0040] M 1 6-e M 2 M 3 5-e+f X 1+e-2f
[0041] (In the chemical formula 3, M 1 is at least one selected from Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba and mixtures thereof, M 2 is at least one selected from P, N, Al, Si, Ga, Ge, As, In, Sn, Sb, Pb, Bi and mixtures thereof, M 3 is S, O or a mixture thereof, X is one or more elements selected from Group 17 elements, 0.3≤e≤1, -0.2≤f≤0.2).
[0042] In addition, the negative electrode active material may include at least one selected from SiO a1 (0 < a1 ≤ 2), SiC a2 (0 < a2 ≤ 2), lithium titanium composite oxide (LTO), artificial graphite, and natural graphite.
[0043] The lithium titanium composite oxide may include at least one selected from Li 4 Ti 5 O 12 、Li 0.8 Ti 2.2 O 4 、Li 8 Ti 4 O 12 and LiTi 2 O 4 among others.
[0044] The negative electrode can be manufactured by coating a slurry for the negative electrode, which contains a negative electrode active material, a second internal solid electrolyte, a binder, a conductive material, a dispersant, and a solvent, etc., on a negative electrode current collector.
[0045] The binder, conductive material, dispersant, and solvent can be the same as those described for the positive electrode.
[0046] The negative electrode current collector can be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, carbon, nickel, titanium, silver, etc., substances for surface - treating the surface of copper or stainless steel, aluminum - cadmium alloy, etc.
[0047] The all - solid - state battery according to the present invention includes a positive electrode laminate portion in which a first external solid electrolyte layer is formed on at least one side of the positive electrode and is independently manufactured, and a negative electrode laminate portion in which a second external solid electrolyte layer is formed on at least one side of the negative electrode and is independently manufactured. Therefore, compared with the case where electrodes - solid electrolyte layer - electrodes are sequentially laminated and rolled, even if there is an external impact or a volume change of the electrodes during charge and discharge, physical detachment between each electrode and each external solid electrolyte layer can be suppressed. Specifically, when the first external solid electrolyte layer is formed on the positive electrode and the second external solid electrolyte layer is formed on the negative electrode, the slurry for the positive electrode and the slurry for the negative electrode are bonded to the positive electrode and the negative electrode respectively through the binder during the drying process, thereby preventing physical detachment.
[0048] In addition, the first outer solid electrolyte layer of the positive electrode laminate and the second outer solid electrolyte layer of the negative electrode laminate respectively form a layer structure in the form of a thin film containing a sulfide-based solid electrolyte having a chemical composition different from each other, and are in face-to-face contact with each other, so that compared with the case where a solid electrolyte in a slurry state is applied to each electrode and rolled, even after rolling, the components of each solid electrolyte layer having a chemical composition different from each other will not be mixed, and each can independently maintain its inherent chemical composition. More specifically, in the present invention, the first outer solid electrolyte layer of the positive electrode laminate contains a sulfide-based solid electrolyte that is stable in the positive electrode operating voltage range of about 2.5-4.3V, and the second outer solid electrolyte layer of the negative electrode laminate contains a sulfide-based solid electrolyte that is stable in the negative electrode operating voltage range of about 0-1.0V, thereby improving the stability at the interfaces of the positive and negative electrodes, so that not only the side reactions at each interface can be suppressed, but also the ion transfer resistance can be effectively reduced. On the other hand, as in the prior art, when a solid electrolyte is coated between the positive electrode and the negative electrode and rolled, the solid electrolyte is required to maintain stability within a wide voltage range of about 0-4.5V, but sulfide-based solid electrolytes are difficult to maintain stability within the above voltage range, and thus side reactions are prone to occur at the electrode interface, thus posing the problem of reduced performance of all-solid-state batteries.
[0049] According to another embodiment of the present invention, a method for manufacturing an all-solid-state battery includes the following steps: forming a positive electrode stacking portion having a first external solid electrolyte layer provided on at least one side of a positive electrode; forming a negative electrode stacking portion having a second external solid electrolyte layer provided on at least one side of a negative electrode; and bringing the first external solid electrolyte layer of the positive electrode stacking portion and the second external solid electrolyte layer of the negative electrode stacking portion into face-to-face contact with each other and rolling, wherein the first external solid electrolyte layer and the second external solid electrolyte layer contain sulfide-based solid electrolytes having different chemical compositions from each other.
[0050] First, a step of forming a positive electrode laminated portion in which a first outer solid electrolyte layer is provided on at least one surface of a positive electrode is performed.
[0051] The positive electrode may include a positive electrode active material and a first internal solid electrolyte.
[0052] The first inner solid electrolyte and the first outer solid electrolyte may each independently include a compound represented by Chemical Formula 1 below.
[0053] [Chemical formula 1]
[0054] M 1 6-a M 2 M 3 5-a+bX 1+a-2b
[0055] (In the chemical formula 1, M 1 is at least one selected from Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba and mixtures thereof, M 2 is at least one selected from P, N, Al, Si, Ga, Ge, As, In, Sn, Sb, Pb, Bi and mixtures thereof, M 3 is S, O or a mixture thereof, X is one or more elements selected from Group 17 elements, -1≤a<0.3, -0.2≤b≤0. )
[0056] The positive active material may include a compound represented by Chemical Formula 2 below.
[0057] [Chemical formula 2]
[0058] Li 1+c M 4 x M 5 y M 6 z O d
[0059] (In the chemical formula 2, -0.05≤c≤0.2, 2≤d≤2.02, 0≤x≤1, 0≤y≤0.5, 0≤z≤0.5, x+y+z=1, M 4 、M 5 and M 6 is at least one selected from Ni, Co, Mn, Na, Mg, Ca, Ti, V, Cr, Cu, Zn, Ge, Sr, Ag, Ba, Zr, Nb, Mo, Al, Ga and B. )
[0060] The positive electrode can be manufactured by coating a slurry for a positive electrode including a positive electrode active material, a first internal solid electrolyte, a binder, a conductive material, a dispersant, a solvent, etc. on a positive electrode collector. Specifically, the positive electrode active material, the first internal solid electrolyte, the binder, the conductive material, and the dispersant are dispersed in a solvent to prepare a slurry for forming a positive electrode, and the slurry is coated on the positive electrode collector and dried, thereby manufacturing the positive electrode.
[0061] The binder may include, for example, one or more selected from polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber and copolymers thereof.
[0062] The conductive material may include graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, etc.; conductive fibers such as carbon fiber or metal fiber; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc., but are not necessarily limited to these. Any material can be used as long as it is a conductive material that does not cause chemical changes to the battery.
[0063] The dispersant may be a water-based dispersant or an organic dispersant such as N-methyl-2-pyrrolidone (NMP).
[0064] The solvent may be, for example, one selected from toluene, xylene, naphtha, benzene, chlorobenzene, and a mixed solvent thereof, but is not necessarily limited thereto.
[0065] The positive electrode current collector may be made of, for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or a material obtained by surface-treating the surface of aluminum or stainless steel with carbon, nickel, titanium, silver, or the like.
[0066] The slurry can be applied by a known coating method such as a slot die coating method, a knife coating method, a dipping method, a reverse roll coating method, a forward roll coating method, a gravure coating method, an extrusion method, a brush coating method, or the like.
[0067] The drying may be performed by natural drying, hot air drying, cold air drying, or heating drying to volatilize the solvent, but is not necessarily limited thereto as long as a positive electrode in a solidified state can be produced by evaporating the solvent in the slurry.
[0068] The drying may be performed at 50-150°C.
[0069] The step of forming the positive electrode laminate may include applying a slurry for forming a first external solid electrolyte layer, which includes a first external solid electrolyte, a binder, and a dispersant, to at least one side of the positive electrode and drying the slurry. Specifically, the first external solid electrolyte, the binder, and the dispersant may be dispersed in a solvent to prepare a slurry for forming the first external solid electrolyte layer, and the slurry may be applied to at least one side of the positive electrode and dried.
[0070] The binder, dispersant and solvent may be the same as those described above for the method of manufacturing the positive electrode.
[0071] The method of coating the slurry for forming the first outer solid electrolyte layer on at least one side of the positive electrode is not particularly limited, and the same method as the method of coating the slurry for forming the positive electrode on the positive electrode collector may be used.
[0072] Drying during the manufacture of the positive electrode laminate can also use the same drying methods and conditions as those for the manufacture of the positive electrode.
[0073] Next, a step of forming a negative electrode laminate in which a second external solid electrolyte layer is provided on at least one surface of the negative electrode is performed.
[0074] The negative electrode may contain a negative electrode active material and a second internal solid electrolyte.
[0075] The second internal solid electrolyte and the second external solid electrolyte may each independently contain a compound represented by the following Chemical Formula 3.
[0076] [Chemical Formula 3]
[0077] M 1 6-e M 2 M 3 5-e+f X 1+e-2f
[0078] (In the Chemical Formula 3, M 1 is at least one selected from Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba, and mixtures thereof, M 2 is at least one selected from P, N, Al, Si, Ga, Ge, As, In, Sn, Sb, Pb, Bi, and mixtures thereof, M 3 is S, O, or a mixture thereof, X is one or more elements selected from Group 17 elements, 0.3 ≤ e ≤ 1, -0.2 ≤ f ≤ 0.2.)
[0079] The negative electrode active material may contain at least one selected from SiO a1 (0 < a1 ≤ 2), SiC a2 (0 < a2 ≤ 2), lithium titanium composite oxide (LTO), artificial graphite, and natural graphite.
[0080] The lithium titanium composite oxide may contain at least one selected from Li 4 Ti 5 O 12 、Li 0.8 Ti 2.2 O 4 、Li 8 Ti 4 O 12 、LiTi 2 O 4 and LiTi
[0081] The negative electrode can be manufactured by coating a slurry for a negative electrode including a negative electrode active material, a second internal solid electrolyte, a binder, a conductive material, a dispersant, a solvent, etc. on a negative electrode collector. Specifically, the negative electrode active material, the second internal solid electrolyte, the binder, the conductive material, and the dispersant are dispersed in a solvent to prepare a slurry for forming a negative electrode, and the slurry is coated on the negative electrode collector and dried, thereby manufacturing the negative electrode.
[0082] The binder, the conductive material, the dispersant, and the solvent may be the same as those described in the method for producing the positive electrode.
[0083] The negative electrode current collector may be made of, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or the like, or aluminum-cadmium alloy.
[0084] The coating and drying of the slurry may be the same as those described in the method for producing the positive electrode.
[0085] The step of forming the negative electrode laminate may include applying a slurry for forming a second external solid electrolyte layer containing a second external solid electrolyte, a binder and a dispersant to at least one side of the negative electrode and drying the slurry. Specifically, the second external solid electrolyte, the binder and the dispersant are dispersed in a solvent to prepare a slurry for forming a second external solid electrolyte layer, and the slurry is applied to at least one side of the negative electrode and dried.
[0086] The binder, dispersant and solvent may be the same as those described above for the method of manufacturing the negative electrode.
[0087] The application and drying of the slurry for forming the second outer solid electrolyte layer may be the same as those described in the step of forming the positive electrode laminate.
[0088] After forming a positive electrode laminate and a negative electrode laminate on the positive electrode and the negative electrode, respectively, a step of bringing the first outer solid electrolyte layer of the positive electrode laminate and the second outer solid electrolyte layer of the negative electrode laminate into face-to-face contact with each other and rolling is performed.
[0089] The calendering may be performed at a pressure of 100-600 MPa, preferably at a pressure of 200-550 MPa, and more preferably at a pressure of 400-500 MPa.
[0090] The calendering can be performed by a known method such as compaction, roll pressing, isostatic pressing, etc.
[0091] As described above, a positive electrode having a positive electrode stacking portion and a negative electrode having a negative electrode stacking portion are manufactured separately, and then rolled in a manner that allows the positive electrode stacking portion and the negative electrode stacking portion to be in face-to-face contact. Therefore, according to the all-solid-state battery of the present invention, even if the volume of the electrode changes due to external impact or during charging and discharging, physical detachment between each electrode and each external solid electrolyte layer can be suppressed.
[0092] In particular, the first external solid electrolyte layer and the second external solid electrolyte layer are formed in the form of thin films on the positive electrode and the negative electrode, respectively, and the electrolyte layers are stacked and rolled in a manner that the electrolyte layers are in face-to-face contact with each other, so that the components of the solid electrolyte layers with different chemical compositions can not be mixed, and can each independently maintain an inherent chemical composition, so that the electrochemical stability at the interface between each external solid electrolyte layer and the electrode can be ensured. Specifically, when the first external solid electrolyte layer is formed on the positive electrode and the second external solid electrolyte layer is formed on the negative electrode, the slurry for the positive electrode and the slurry for the negative electrode are respectively bonded to the positive electrode and the negative electrode by a binder during the drying process, so that physical shedding can be prevented.
[0093] Furthermore, after the rolling step, the first outer solid electrolyte layer of the positive electrode laminate portion and the second outer solid electrolyte layer of the negative electrode laminate portion may be in contact with each other in an inseparable manner.
[0094] The first outer solid electrolyte layer of the positive electrode laminate part and the second outer solid electrolyte layer of the negative electrode laminate part include sulfide-based solid electrolytes having chemical compositions different from each other, and the sulfide-based solid electrolytes may include a compound having an argyrodite crystal structure.
[0095] Hereinafter, the present invention will be described in more detail by way of examples, but these examples are only for the purpose of helping to understand the present invention, and the scope of the present invention is not limited to these examples in any sense.
[0096] <Example 1> Manufacturing of all-solid-state battery 1
[0097] As the solid electrolyte (first internal solid electrolyte) contained in the positive electrode, Li 6 PS 5 Cl, LiNi as positive electrode active material 0.8 Co 0.1 Mn 0.1 O 2 , carbon black as a conductive material and butadiene rubber as a binder, which are mixed with a solvent, o-xylene, to prepare a slurry for forming a positive electrode, and the slurry is coated on an aluminum foil as a positive electrode collector using a doctor blade, and then dried at 120° C. for 10 minutes.
[0098] Then, Li as a solid electrolyte (first external solid electrolyte) provided on the positive electrode 6 PS 5 Cl and butadiene rubber as a binder were mixed with o-xylene as a solvent, then coated on the positive electrode and dried at 120° C. for 10 minutes to form a first outer solid electrolyte layer on the positive electrode. Thereafter, the positive electrode laminate was vacuum dried at 120° C. for 4 hours.
[0099] In addition, Li 2 O 2 is used as a solid electrolyte (second internal solid electrolyte) contained in the negative electrode. 5.4 PS 4.4 Cl 1.6 , a silicon-graphite composite as a negative electrode active material and butadiene rubber as a binder, which are mixed with a solvent, o-xylene, to prepare a slurry for forming a negative electrode, and the slurry is coated on a nickel foil as a negative electrode current collector using a doctor blade, and then dried at 120°C for 10 minutes.
[0100] Then, Li as a solid electrolyte (second external solid electrolyte) provided on the negative electrode 5.4 PS 4.4 Cl 1.6 The butadiene rubber as a binder was mixed with o-xylene as a solvent, then coated on the negative electrode and dried at 120° C. for 10 minutes to form a second outer solid electrolyte layer on the negative electrode. Thereafter, the negative electrode laminate was vacuum dried at 120° C. for 4 hours.
[0101] The negative electrode formed with the second outer solid electrolyte layer is arranged so that the second outer solid electrolyte layer faces upward, and the positive electrode formed with the first outer solid electrolyte layer is stacked on the second outer solid electrolyte layer so that the first outer solid electrolyte layer and the second outer solid electrolyte layer face each other. After that, a warm isostatic press is used to perform rolling at 90°C and 450MPa to manufacture an all-solid-state battery.
[0102] <Example 2> Manufacturing of all-solid-state battery 2
[0103] An all-solid-state battery was manufactured by the same method as in Example 1, except that Li 5.4 PS 4.4 Cl 1.6 , instead of Li 6 PS 5 Cl.
[0104] <Example 3> Manufacturing of all-solid-state battery 3
[0105] An all-solid-state battery was manufactured by the same method as in Example 1, except that Li 5.7 PS 4.7 Cl 1.3 , instead of Li 6 PS 5 Cl.
[0106] <Comparative Example 1> Production of All-Solid State Battery 4
[0107] An all-solid-state battery was manufactured by the same method as in Example 1, except that the first external solid electrolyte was not contained in the positive electrode laminated part.
[0108] <Experimental Example 1> Evaluation of the Charge and Discharge Performance of All-Solid State Batteries
[0109] In order to evaluate the charge and discharge performance of the all-solid-state battery, the all-solid-state batteries according to Examples 1 to 3 and Comparative Example 1 were charged and discharged once at 30°C at a 0.05C rate. As a result, the voltage profile is shown in FIG. Figure 3 and in the following Table 1. The resistance value was calculated by discharging at 0.33C for 10 seconds at a 50% state of charge (DC-IR).
[0110] [Table 1]
[0111]
[0112] The experimental results confirmed that the all-solid-state batteries according to Examples 1 to 3 using a positive electrode with a first external solid electrolyte layer formed thereon not only had excellent charge capacity, discharge capacity, and average discharge voltage, but also had low resistance values, compared to the all-solid-state battery according to Comparative Example 1 in which the first external solid electrolyte layer was not formed alone on the positive electrode. It is presumed that this is because the first external solid electrolyte layer formed on one side of the positive electrode and the second external solid electrolyte layer formed on one side of the negative electrode maintain close contact with the positive electrode and the negative electrode, respectively, even when charging and discharging are performed.
[0113] In addition, when Example 1 is compared with Example 2 and Example 3, the effect of the type of the first external solid electrolyte used in the positive electrode can be confirmed. Specifically, Li 6 PS 5 In the case of Example 1 using Li 5.4 PS 4.4 Cl 1.6 or Li 5.7 PS 4.7 Cl 1.3Compared with Example 2 and Example 3, the embodiment 1 shows excellent charge and discharge efficiency and low resistance. That is, considering that Li 5.4 PS 4.4 Cl 1.6 As the second external solid electrolyte formed on one side of the negative electrode, it can be confirmed that when Li 6 PS 5 All-solid-state batteries perform best when the first outer solid electrolyte layer of Cl is in face-to-face contact with the positive electrode. This is because Li 6 PS 5 Cl has excellent oxidation stability and Li 5.4 PS 4.4 Cl 1.6 Excellent reduction stability.
[0114] <Experimental Example 2> Evaluation of Life Characteristics of All-Solid-State Batteries
[0115] In order to evaluate the life characteristics of the all-solid-state battery, for the all-solid-state batteries according to Examples 1 to 3 and Comparative Example 1, the capacity during the cycle was measured and shown in Table 2 below, and the capacity retention rate with the progress of the cycle is shown in Figure 4 Initially, the charge and discharge were performed at a rate of 0.1C, and then at a rate of 0.2C.
[0116] [Table 2]
[0117]
[0118] In the case of the all-solid-state battery according to Example 1, about 90% of the initial capacity (capacity of the second cycle) is maintained even after 50 cycles, and thus, even after repeated multiple charge and discharge cycles, the capacity retention rate is excellent compared to the all-solid-state battery according to Comparative Example 1. In addition, in the case of the all-solid-state battery according to Example 1, an excellent capacity retention rate is also shown compared to the all-solid-state batteries according to Examples 2 and 3.
[0119] That is, it was confirmed that the Li 6 PS 5 The solid electrolyte layer of Cl and the Li 5.4 PS 4.4 Cl 1.6 In the case of a stacked structure all-solid-state battery in which a solid electrolyte layer is in face-to-face contact with a positive electrode, a solid electrolyte layer is not formed on the positive electrode or a Li 5.4 PS 4.4 Cl 1.6 or Li 5.7 PS 4.7 Cl1.3 The capacity retention rate is better than that of the solid electrolyte layer.
[0120] In the case of Example 1, the highest capacity ratio was shown at the 0.2C rate compared to the 0.05C rate. Such a capacity expression at a high rate is also related to the above-mentioned low resistance value.
Claims
1. An all-solid-state battery, comprising: a positive electrode laminated portion including a positive electrode and a first outer solid electrolyte layer formed on at least one side of the positive electrode; and a negative electrode laminated portion including a negative electrode and a second outer solid electrolyte layer formed on at least one side of the negative electrode, wherein the first outer solid electrolyte layer of the positive electrode laminate portion and the second outer solid electrolyte layer of the negative electrode laminate portion are in face-to-face contact with each other, The first outer solid electrolyte layer and the second outer solid electrolyte layer contain sulfide-based solid electrolytes having chemical compositions different from each other.
2. The all-solid-state battery according to claim 1, wherein: The first outer solid electrolyte layer of the positive electrode laminate portion and the second outer solid electrolyte layer of the negative electrode laminate portion are in contact with each other in a manner not to be mixed with each other and not to be physically separated from each other.
3. The all-solid-state battery according to claim 1, wherein: The sulfide-based solid electrolyte includes a compound having an argyrodite crystal structure.
4. The all-solid-state battery according to claim 1, wherein: The positive electrode includes a positive electrode active material and a first internal solid electrolyte.
5. The all-solid-state battery according to claim 1, wherein: The negative electrode includes a negative electrode active material and a second internal solid electrolyte.
6. The all-solid-state battery according to claim 4, wherein: The first inner solid electrolyte and the first outer solid electrolyte each independently include a compound represented by the following Chemical Formula 1: [Chemical formula 1] M 1 6-a M 2 M 3 5-a+b X 1+a-2b In the chemical formula 1, M 1 is at least one selected from Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba and mixtures thereof, M 2 is at least one selected from P, N, Al, Si, Ga, Ge, As, In, Sn, Sb, Pb, Bi and mixtures thereof, M 3 is S, O or a mixture thereof, X is one or more elements selected from Group 17 elements, -1≤a<0.3, -0.2≤b≤0.
7. The all-solid-state battery according to claim 5, wherein: The second inner solid electrolyte and the second outer solid electrolyte each independently include a compound represented by the following Chemical Formula 3: [Chemical formula 3] M 1 6-e M 2 M 3 5-e+f X 1+e-2f In the chemical formula 3, M 1 is at least one selected from Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba and mixtures thereof, M 2 is at least one selected from P, N, Al, Si, Ga, Ge, As, In, Sn, Sb, Pb, Bi and mixtures thereof, M 3 is S, O or a mixture thereof, X is one or more elements selected from Group 17 elements, 0.3≤e≤1, -0.2≤f≤0.
2.
8. The all-solid-state battery according to claim 4, wherein: The positive electrode active material includes a compound represented by the following Chemical Formula 2: [Chemical formula 2] Li 1+c M 4 x M 5 y M 6 z O d In the chemical formula 2, -0.05≤c≤0.2,2≤d≤2.02, 0≤x≤1, 0≤y≤0.5, 0≤z≤0.5, x+y+z=1, M 4 、M 5 and M 6 It is at least one selected from Ni, Co, Mn, Na, Mg, Ca, Ti, V, Cr, Cu, Zn, Ge, Sr, Ag, Ba, Zr, Nb, Mo, Al, Ga and B.
9. The all-solid-state battery according to claim 5, wherein: The negative electrode active material contains at least one selected from SiO a1 , where 0 < a1 ≤ 2, SiC a2 , where 0 < a2 ≤ 2, lithium titanium composite oxide (LTO), artificial graphite, and natural graphite.
10. A method for manufacturing an all-solid-state battery, comprising the following steps: forming a positive electrode laminated portion having a first outer solid electrolyte layer provided on at least one side of the positive electrode; forming a negative electrode laminated portion in which a second outer solid electrolyte layer is provided on at least one side of the negative electrode; and The first outer solid electrolyte layer of the positive electrode laminate portion and the second outer solid electrolyte layer of the negative electrode laminate portion are brought into contact with each other face to face and rolled, Herein, the first outer solid electrolyte layer and the second outer solid electrolyte layer include sulfide-based solid electrolytes having chemical compositions different from each other.
11. The method for manufacturing an all-solid-state battery according to claim 10, wherein: After the rolling step, the first outer solid electrolyte layer of the positive electrode laminate portion and the second outer solid electrolyte layer of the negative electrode laminate portion are in contact with each other in a manner not to be mixed with each other and not to be physically separated from each other.
12. The method for manufacturing an all-solid-state battery according to claim 10, wherein: The sulfide-based solid electrolyte includes a compound having an argyrodite crystal structure.
13. The method for manufacturing an all-solid-state battery according to claim 10, wherein: The positive electrode includes a positive electrode active material and a first internal solid electrolyte.
14. The method for manufacturing an all-solid-state battery according to claim 10, wherein: The negative electrode includes a negative electrode active material and a second internal solid electrolyte.
15. The method for manufacturing an all-solid-state battery according to claim 10, wherein: The step of forming the positive electrode laminated portion includes applying a slurry for forming a first external solid electrolyte layer, which includes a first external solid electrolyte, a binder, and a dispersant, on at least one side of the positive electrode and drying the slurry.
16. The method for manufacturing an all-solid-state battery according to claim 10, wherein: The step of forming the negative electrode laminate includes applying a slurry for forming a second external solid electrolyte layer, which contains a second external solid electrolyte, a binder, and a dispersant, on at least one side of the negative electrode and drying the slurry.
17. The method for manufacturing an all-solid-state battery according to claim 15 or 16, wherein: The drying is carried out at 50-150°C.
18. The method for manufacturing an all-solid-state battery according to claim 10, wherein: The calendering is performed at a pressure of 100-600 MPa.